Upaya Peningkatan Hasil Belajar Matematika Siswa Kelas VII melalui Model Discovery Learning SMPN 5 Bonai Darussalam - Sri Haryati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The purpose of this study is to improve the mathematics learning outcomes of grade VII students through the application of the discovery learning learning model. The type of research is classroom action research (PTK), with the subjects in this study being grade VII students of SMP Negeri 5 Bonai Darussalam for the 2021/2022 school year totaling 25 students. Data from the study were collected through observation and tests from each cycle. This study lasted for two cycles and previously carried out the pre-cycle stage. Actions are said to be successful if the learning outcomes meet the minimum completeness criteria of 65 with a percentage of completeness of 80%. The data collection technique used is in the form of description test questions and learning implementation observation sheets. Furthermore, an analysis of the data that has been obtained is carried out. The results showed that the application of the discovery learning learning model can improve student learning outcomes. This is evidenced by the increase in learning outcomes from cycle I to cycle II. In the pre-cycle the average obtained was 61.75. In Cycle I, the average obtained was 76.50 with a percentage of completeness of learning outcomes of 76 %. While the learning outcomes of cycle II with an average of 90.85 with a percentage of completeness of learning outcomes of 88%. Based on the results of this study, it can be concluded that mathematics learning outcomes increase by applying the discovery learning learning model to grade VII students of SMP Negeri 5 Bonai Darussalam for the 2021/2022 school year.